2000
DOI: 10.1007/s004390000318
|View full text |Cite
|
Sign up to set email alerts
|

Structure and polymorphism of the human gene for the interferon-induced p78 protein (MX1): evidence of association with alopecia areata in the Down syndrome region

Abstract: Alopecia areata (AA) is a chronic inflammatory disease characterised by patchy hair loss with T cell infiltration of hair follicles. AA occurs in approximately 0.1% of the general population, but this is increased to 9% in Down syndrome (DS). DS is associated with an additional copy (full or partial) of chromosome 21, and the DS region may potentially include genes involved in the pathogenesis of AA. MX1 is the gene encoding the interferon-induced p78 protein (MxA). MxA protein confers resistance to influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 38 publications
2
51
1
2
Order By: Relevance
“…The human MX1 gene is highly conserved and only a few single nucleotide polymorphisms are described in the human population (57). However, a recent study analyzing variations in the MxA genes of 267 healthy individuals identified two rare nucleotide changes that result in amino acid exchanges at positions 255 and 268 (50).…”
Section: Discussionmentioning
confidence: 99%
“…The human MX1 gene is highly conserved and only a few single nucleotide polymorphisms are described in the human population (57). However, a recent study analyzing variations in the MxA genes of 267 healthy individuals identified two rare nucleotide changes that result in amino acid exchanges at positions 255 and 268 (50).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour necrosis factor α (TNF-α) gene polymorphism, or adjacent genes in the HLA region, might also influence AA susceptibility (Refs 86, 87). More-recent gene association studies have identified specific polymorphisms in the genes encoding MX1, AIRE and NOTCH4 ( Refs 88,89,90).…”
Section: Genetic Association Studies In Aamentioning
confidence: 98%
“…There was no sequence alteration in the tripartite GTPase domain or the self-assembly domains. The difference observed may be the result of human sequence polymorphisms (24). MxA expression has only been reported following viral infection or treatment with IFNs (3-5).…”
Section: Constitutive Expression Of Mxa In Pc-3 Cells-dd-rt-pcrmentioning
confidence: 99%